Differential perception of virulence factors of uropathogenic Escherichia coli at the level of chromatin dynamics of infected host cells - Mukherjee, Krishnendu; Aschenbach, Wiebke; Hilger, Annika; Saur, Judith; Dobrindt, Ulrich (Frontiers in Immunology, 2025)
IntroductionUropathogenic Escherichia coli (UPEC) evades the innate immune response in the urinary tract through the coordinated action of various virulence factors encoded within distinct pathogenicity islands (PAIs). We have demonstrated that UPEC infection leads to the epigenetic regulation of host gene expression; however, the specific role of PAI-encoded virulence factors in this process remains largely unexplored.MethodsIn this follow-up study, we infected Galleria mellonella larvae with individual PAI deletion mutants of UPEC strain 536 to investigate the relationship between UPEC virulence determinants and host epigenetic regulation.ResultsThe loss of different pathogenicity islands (PAI I536 to PAI VI536) led to varying degrees of virulence attenuation in larvae and an increased sensitivity to G. mellonella hemolymph compared to the wild-type UPEC strain 536. Notably, infection with the different PAI mutants resulted in distinct histone modification patterns, including hypo- or hyper-acetylation of specific histone H3K9 and H4K5 residues. In addition, the loss of selected PAIs led to altered expression of histone acetyltransferases and histone deacetylases as well as changes in the expression of antimicrobial innate immune genes. We show that UPEC-induced histone acetylation changes in larvae were conserved in human bladder epithelial cells, underscoring the translational relevance of the G. mellonella system.DiscussionThese findings reveal that specific PAI-encoded virulence factors trigger epigenetic and immunological changes in G. mellonella which may help us to also better understand relevant processes in the course of infection in humans.